1993
DOI: 10.1182/blood.v81.2.496.bloodjournal812496
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Epstein-Barr virus in the Reed-Sternberg cells of Hodgkin's disease occurring in Peru

Abstract: The Epstein-Barr virus (EBV) has been implicated in the pathogenesis of Hodgkin‧s disease (HD). This study was undertaken to determine whether the association of EBV with HD showed geographical variation, as in Burkitt‧s lymphoma. We studied 32 formalin-fixed, paraffin-embedded cases of HD occurring in Peru. EBV DNA-RNA in situ hybridization was performed using a 30-base biotinylated antisense oligonucleotide complementary to the EBER1 gene of EBV. EBV immunohistochemistry was also performed, using a monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
2
17
1
1
Order By: Relevance
“…Association between HD and EBV has been demonstrated in epidemiologic, serologic, and molecular biologic studies 6‐12. In particular, in developing countries with high incidences of HD,13‐15 the detection rate of EBV in HD is even higher. However, no such association is observed in the developed countries, in spite of the higher incidence of HD,24‐34 which makes up a larger percentage of all the malignant lymphomas occurring in these countries 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association between HD and EBV has been demonstrated in epidemiologic, serologic, and molecular biologic studies 6‐12. In particular, in developing countries with high incidences of HD,13‐15 the detection rate of EBV in HD is even higher. However, no such association is observed in the developed countries, in spite of the higher incidence of HD,24‐34 which makes up a larger percentage of all the malignant lymphomas occurring in these countries 1…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of EBV infection in patients with HD varies widely. Although it could be detected in nearly 100% of patients with HD in developing countries13‐15 as well as in Orientals,16‐19 it was only detected in approximately 45% of HD cases in developed countries.…”
mentioning
confidence: 99%
“…In two other ISH studies of HD patients (19,90), EBV nucleic acids were detected in RS cells of 94 to 100% tissue specimens from Latin American children but only in 36% of those from U.S. children (19). The combined results of these and many other investigations of the frequency of association of EBV and HD have suggested that variations in frequency are linked to geography and socioeconomic criteria, age, ethnicity, immunosuppression, and histologic subtypes (19,66,88,90,124,206,212,216,245,352,369,375,393,395,518,522,544,572). By analogy to EBV, differences between studies in the observed frequencies of detection of HHV-6 in specimens from HD patients might result from any of a variety of factors.…”
Section: Neoplasiamentioning
confidence: 92%
“…There has been a decline in incidence rates among the elderly due to a decline in misclassification between HD and NHL. 57 The known or suspected risk factors for HD relate to occupational exposures among farmers or forestry workers, 59 socioeconomic status; 60 medical history, including late onset of certain childhood viral diseases, 61 infectious mononucleosis, 62 or Epstein-Barr virus positivity [63][64][65] , previous cancer, 66 organ transplant, 67 and HIV or AIDS; 68 a positive family history of cancer or immune deficiency in a first-degree relative 69 -71; and a dose-response pattern for a diagnosis of lymphoma/leukemia in any first-degree relative, which increases if a sibling has HD. 72,73 Epidemiologic studies of hematopoietic and lymphatic tumors in association with occupational exposure to animals have produced conflicting results including positive, negative and no effect.…”
Section: Discussionmentioning
confidence: 99%